Grid reconnection detection for synchronous distributed generators in stand‐alone operation. (31st October 2013) - Jouybari‐Moghaddam, Hessamoddin; Hosseinian, Seyed Hossein; Vahidi, Behrooz
Summary Industrial plants/commercial facilities with synchronous generation, seek reliable and continuous operation even at the time of grid outages. Thus, islanding detection methods have been proposed in the literature that can be used to change the operating mode of the employed distributed generators from grid‐parallel to stand‐alone. Among the few solutions previously presented for switching the control mode in the reverse event of reconnecting to the grid, the method presented in this paper is unique. This grid‐reconnection detection technique is low cost, fast, and does not interact with the power quality of the island although it only uses one, locally measured, variable. The method implies processing of oscillatory modes in frequency signal and is independent of the autonomous island's boundary. The investigation also includes a discussion on similar event of merging of adjacent islands. Simulations confirm the successful discrimination between reconnection event and other switching/power quality events. Copyright © 2013 John Wiley & Sons, Ltd.